MEMBACA WACANA KAJIAN AL-QUR’AN DAN TAFSIR DI KALANGAN SARJANA BARAT: Analisis Pemikiran Andrew Rippin - Rizal Faturohman Purnama; Rizal Samsul Mutaqin (UIN Siber Syekh Nurjati Cirebon, 2021)
The development of the study of Qur’an in line with the rise of Islam in the middle ages, the west sought to understanding Islam. As the entrance to understanding Islam through the study of Qur'an. The first western study of the Qur’an was the translation of Qur'anic text into Latin and Other European Languages. Then it developed into another study of Qur'an. This paper answers how the origins of the study of Qur’an among Western scholars. And how the dynamics of the study of the Qur’an in the West occurred. this article got to the point of discovering that, there are three models of Qur'anic studies that are popular and developed among Western scholars. first, studies that seek To find Jewish-Christian influence in Qur'an. Second, a study that completes the chronological sequence of verses of Qur'an. Third, studies that discuss the mismanagement or certain aspects of Qur'an.